Effect of Giving Snakehead Fish Extract (Channa striata) on Albumin, Neutrophil, and Lymphocyte Levels in Hypoalbuminemia Patients - Mustafa, Annasari; Khoirunnisa, Ailsa Amelia; Rahman, Nur (Journal of Local Therapy, 2022)
Hypoalbuminemia is a condition where the albumin level in the blood falls below normal. Hypoalbuminemia is known as a marker of protein energy malnutrition, inflammation, infection, liver disease, kidney disease and postoperative stress. In Indonesia, malnutrition hospital data shows 40-50% of patients have hypoalbuminemia or are at risk of hypoalbuminemia, 12% of them are severe hypoalbuminemia, and the hospitalization period for patients with hospital malnutrition shows 90% longer than patients with good nutrition. Decreased albumin levels can be associated with a decrease in the immune system and slow healing of tissues/wounds due to infection. Neutrophils and lymphocytes whose numbers increase when inflammation occurs. Oral administration of high protein with snakehead fish extract (Channa striata ) is an alternative treatment for hypoalbuminemia. Objective: The purpose of this study was to determine the effect of snakehead fish extract (Channa striata) on albumin, neutrophil, and lymphocyte levels in hypoalbuminemic patients. Method: Articles are compiled using a systematic method literature review , involving national and international journals by taking journals through Google scholar, Pubmed, Research Gate, Scient direct. Results: There was an effect of giving snakehead fish extract on albumin levels, neutrophil values, and lymphocyte values in hypoalbuinemic patients and experimental animals. Conclusion: The content of amino acids, albumin, Zn, Fe, Cu and unsaturated fatty acids in snakehead fish ( Ophiocephalus striatus) is quite effective as an effort to increase albumin levels, decrease neutrophil and lymphocyte values when inflammation occurs in hypoalbuminemic patients